Influence of load feature on the water distribution system in a centralized air-conditioning system. (17th February 2017) - Zhou, Xin; Yan, Da
Abstract : On-site investigations show that an asynchronous load feature would greatly influence the operation of water systems for centralized air conditioning. However, the manner of defining the load feature and relating it to its influence quantitatively is still unclear. This article quantitatively describes the asynchronous load demand feature and reveals its relationship with the loss of pump power and heat transfer ability in a centralized air-conditioning water system. The Lorenz curve and the Gini index are introduced in this study and used as indices to depict load features. For a large-scale use in office buildings, shopping malls, and other buildings, the fan coil unit and the variable air volume systems are investigated in this study. The loss of pump power on valves and heat transfer ability under different load profiles are analyzed. This study develops a new perspective of analyzing load patterns and quantitatively explores reasons for the resulting losses in pump power and heat transfer ability in centralized air-conditioning water systems. The method proposed in this article can be used to analyze a number of design problems of chilled water circulation systems such as the zoning of air-conditioning systems and the determination of operational and control strategies.